Pengaruh Penerapan Media Pembelajaran Pop-Up Book Terhadap Motivasi Dan Hasil Belajar IPA Peserta Didik Kelas V SDN 3 Kawo Tahun Ajaran 2020/2021 - Tuwijati, Sir’aini Salim; Ilhamdi, H. Muhammad Liwa; Safruddin, Safruddin (Lembaga Penelitian dan Pendidikan Mandala, 2021)
This study aims to determine the effect of the application of pop-up book learning media on the motivation and learning outcomes of fifth grade students at SDN 3 KAWO in the 2020/2021 academic year. The population in this study were all students of class V at SDN 3 KAWO, while the samples were students of class VA as the experimental class and students of class VB as the control class. Data analysis begins with a normality test using the One-Sample Kolmogrov Smirnov formula with a significance level of 5% (0.05) and continues with a homogeneity test further testing the research hypothesis and further testing with a gain-score test. Then the motivational data and learning outcomes were analyzed by Independent t-test. Samples Test to determine the research hypothesis, the results of data analysis obtained a t-count value of 3,241 while the t-table at a significance level of 5% was 2,048 so that the t-count value> t-table, which means that Ha, which states there is an effect of application pop-up book learning media on science learning motivation of fifth grade students at SDN 3 KAWO in the 2020/2021 academic year, was accepted and H0 rejected. And the obtained t-count is 2.209 while the t-table at the 5% significance level is 2.048 so that the t-count value is >t-table, which means that Ha which states that there is an effect of the application of pop-up book learning media on participants' science learning outcomes fifth grade students of SDN 3 KAWO for the academic year 2020/2021, were accepted and H0 was rejected. Then a follow-up test was carried out using gain-score test, the value of learning motivation is 0.403 which is included in the medium category, while the learning outcomes of 0.576 are included in the medium category.